Synthesis of Ordered Mesoporous Carbons and Adsorption Equilibrium of Resorcinol - Ren-Hong, Chen; Ping, Yuan; Xiu-Fang, Wang (Asian Journal of Chemistry, 2012)
Ordered mesoporous carbons were synthesized by using SBA-15 as template, furfuryl alcohol as carbon precursor and oxalic acid as catalyst. The influence of the usage of oxalic acid on the pore structure of the resulting materials was evaluated. Characterizations such as X-ray diffraction, nitrogen sorption, transmission electron microscopy and Raman spectroscopy were carried out. The adsorption behaviour of resorcinol on the obtained ordered mesoporous carbons was investigated. With the increasing usage of oxalic acid, the structural order, unit cell parameter and wall thickness tended to increase but followed by a small decrease. The BET specific surface areas and pore volumes showed decreasing tendency and pore diameters had the smallest value when using 0.1 g of oxalic acid. The adsorption of resorcinol onto ordered mesoporous carbons followed the Langmuir-Freundlich equation.